2016
DOI: 10.1038/ncomms12368
|View full text |Cite
|
Sign up to set email alerts
|

Dectin-1-activated dendritic cells trigger potent antitumour immunity through the induction of Th9 cells

Abstract: Dectin-1 signalling in dendritic cells (DCs) has an important role in triggering protective antifungal Th17 responses. However, whether dectin-1 directs DCs to prime antitumour Th9 cells remains unclear. Here, we show that DCs activated by dectin-1 agonists potently promote naive CD4+ T cells to differentiate into Th9 cells. Abrogation of dectin-1 in DCs completely abolishes their Th9-polarizing capability in response to dectin-1 agonist curdlan. Notably, dectin-1 stimulation of DCs upregulates TNFSF15 and OX4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 42 publications
3
118
2
1
Order By: Relevance
“…Our previous study (Lu et al, 2012) revealed a distinct role for Th9 cells in provoking CD8 + CTL-mediated antitumor immunity in an IL-9-dependent manner, which has been confirmed by multiple studies (Kim et al, 2015; Vegran et al, 2014; Zhao et al, 2016b). However, all these studies used early-stage tumor models, which may not represent clinically relevant scenario for ACT.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our previous study (Lu et al, 2012) revealed a distinct role for Th9 cells in provoking CD8 + CTL-mediated antitumor immunity in an IL-9-dependent manner, which has been confirmed by multiple studies (Kim et al, 2015; Vegran et al, 2014; Zhao et al, 2016b). However, all these studies used early-stage tumor models, which may not represent clinically relevant scenario for ACT.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, subsequent elegant studies also demonstrated the potential for triggering endogenous antitumor Th9 responses in vivo (Kim et al, 2015; Liu et al, 2015; Zhao et al, 2016b), by both an antigen-nonspecific manner via glucocorticoid-induced tumor necrosis factor (TNF) receptor-related protein costimulation and by an antigen-specific manner via vaccination. However, the T cell features of Th9 cells beyond IL-9 production and whether these cells can be used to cure late-stage advanced tumors (a scenario more like that seen clinically) have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, the injection of anti-CD8 antibodies nullified the anti-tumor efficacy of T H 9 cell transfer in vivo. The ability of T H 9 cell-derived IL-9 to drive the activation of anti-cancer CD8 T cells was further confirmed recently as illustrated by Zhao et al, who found that immunization of tumor-bearing mice with dectin-1-activated DCs induced potent anti-tumor responses that depended on Th9 cells and the IL-9-dependent induction of anti-cancer CD8 T cells [28]. …”
Section: Th9 Cell-driven Activation Of Adaptive Anti-cancer Immunitymentioning
confidence: 74%
“…These findings suggest that strategies favoring the generation of T H 9 cell-mediated immune responses may have an important role in the treatment of melanoma in humans. In the light of the latest advances on T H 9 cell anti-tumor properties [28, 32], the use of dendritic cell-based therapeutic cancer vaccines could be considered to generate a T H 9 cell response in cancer patients. Indeed, DC-expressing GITR-L [46] or activated via the dectin-1 signaling pathway [28] may generate a T H 9 cell anti-tumor response that ultimately results in a clinical benefit in cancer patients.…”
Section: The Role Of Th9 Cells In Human Cancersmentioning
confidence: 99%
“…5,6 We recently used dectin-1 agonist curdlan or Scleroglucan to activate mouse bone marrow (BM)-derived immature DCs (CurDCs or SclDCs) and used these DCs to prime naive CD4 C T cells under Th9-polarizing conditions. 7 We found that dectin-1-activated DCs potently promoted the development of Th9 cells, with upregulated expression of IL-9-and Th9-related transcription factor IRF4, but not other Th cell-related cytokines and transcription factors. Importantly, in the in vivo tests, dectin-1-activated DCs but not regular BMDCs stimulated the powerful production of Th9 cells and IL-9.…”
mentioning
confidence: 95%